Determinants of Inbound International Tourism Demand in India: An Econometric Analysis - Mohammad Shadab Hussain, Dr. Deepika Abhijeet Kininge (Journal of Informatics Education and Research, 2025)
This study investigates the key determinants of inbound international tourism demand in India using econometric analysis. Employing time-series data ARDL, the model examines the role of foreign tourist, Indian tourist, foreign direct investment and exchange rates in shaping tourist arrivals. The results reveal that income and trade openness positively influence tourism demand, while high relative prices act as a deterrent. Exchange rate stability emerges as a crucial factor in attracting international tourists. The findings highlight the interdependence between economic factors and tourism flows. Policy implications suggest enhancing infrastructure, ensuring price competitiveness, and promoting India’s image to sustain long-term growth in inbound tourism